Develpment of a theoretical framework to inform measurement of secondary school student engagement with learning - Cavanagh, Rob; Kennish, Penelope; Sturgess, Kylie (AARE, 2008)
This paper reports on the development of theoretical frameworks to inform a quantitative investigation of secondary school student engagement in classroom learning. A process of inductive analysis was applied to theoretical and empirical literature on student engagement and participation. Material were condensed and summarised leading to the proposal of frameworks with content considered important by the researcher for epistemological and methodological reasons. The paper commences by examining some of the conceptions of student engagement and participation found in the literature on these topics. Next, Bio-ecological models of intellectual development and engagement were examined and adapted to explain student engagement. A twelve element Bio-ecological view of student engagement is proposed. The key attributes of Flow Theory and how this can be applied in a two dimensional conceptualisation of student engagement are then explored. The two dimensions are student capability for learning and expectations of student learning for understanding. A series of propositions and expositions are advanced to provide starting point for operationally defining these constructs. Student capability for learning was defined in terms of stuent attributes associated with learning theory constructs - self-esteem, self-concept, resilience, self-regulation, and self-efficacy. The framework of expectations of learning for understanding was based on the six facets of understanding developed by Wiggins and Mctighe (2001) - this provided operational definitions for the sub-constructs comprising this construct. The paper then presents some of the requirements for objective measurement and how these necessitate the presence of particular features in the theoretical frames that will inform instrument development. Finally, the theory underpinning the conceptualisation of student engagement in classroom learning is re-examined in terms of these requirements.